PERSUASION AND COMMUNICATION CAMPAIGNS: OUTLINES OF A COMMUNICATION INTERVENTION STRATEGY FOR CROWD MANAGEMENT AT ISLAMIC HOLY PLACES (MASHA’ER) DURING HAJJ - Khan, Fazal Rahim; Gazzaz, Osman B.; Iqbal, Zafar (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2016)
Based on an overview of over half a century of research on persuasive communication and information campaigns in the West and the assumptions and challenges of a successful communication and information campaign, the present paper basically outlines a holistic communication intervention strategy in the service of crowd management in the holy places (Masha’er). The objectives and characteristics of the strategy in general are described. Theoretical rationale and a prototype of a set of on-site messages for creating a communication ambience in the Arafaat area are also given. These particular messages aim at preventing crowd congestion around the mount al-Rahmah (Jabal al-Rahmah).